PERAN KEPUASAN KERJA DALAM MEMEDIASI HUBUNGAN GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, KESEIMBANGAN KERJA, DAN PRODUKTIVITAS KERJA PADA PEGAWAI BIRO ADMINISTRASI PIMPINAN DI KANTOR GUBERNUR SUMATERA BARAT - Tika Sakina Putri; Elfiswandi; Jhon Veri (Halu Oleo University, 2025)
This study aims to examine the effect of leadership style, organisational culture, and work-life balance on work productivity mediated by job satisfaction. A quantitative approach with hypothesis testing techniques was used in this study. There were 70 samples with the saturated sample technique, namely, all employees of the Chief Administration Bureau at the West Sumatra Governor's Office. Data were collected through distributing questionnaires online and processed using SmartPLS 3.0 software with structural equation modelling techniques. The results showed that organisational culture and work-life balance each had a positive and significant effect on job satisfaction, but not significantly by leadership style. Leadership style and job satisfaction each have a positive and significant effect on work productivity, but are not significantly affected by organisational culture and work balance. The effect of organisational culture and work balance, respectively, on work productivity through mediation of job satisfaction was found to be positive and significant, but insignificant mediation by job satisfaction was found on the relationship between leadership style and work productivity. The implications of the study emphasise the importance of meeting the needs and comfort of employees in government agencies in order to provide good quality work.